"I Would Consult a Doctor, But What the Rabbi Says Goes": Ultra-Orthodox Jews' Relationships with Rabbis and Doctors in Israel - Neriya-Ben Shahar, Rivka (Journal of religion and health, 2024)
We examine relationships among ultra-Orthodox Israeli Jews, their doctors, and rabbis when medical decisions are made. Analyzing excerpts from sixteen focus groups with 128 ultra-Orthodox Jews, we determine how their belief system affects their decisions about whom to trust and follow when the doctor’s instructions contradict the rabbi’s advice. We argue that the strict behaviors described here with regard to relations among doctors, rabbis, and patients, function as social capital that raises the status of ultra-Orthodox Jews as members of an exclusive club that balances health decisions with the social demand to obey their religious leaders.